Teaching reading in rural secondary schools in Sabah: A preliminary study / Jocelyn Yee Vun Lee and Alice Su Chu Wong - Lee, Jocelyn Yee Vun; Wong, Alice Su Chu (Universiti Teknologi MARA, Sabah, 2020)
In language learning, students in rural areas have lower proficiency in English than those in urban areas. The aims of the present study were to investigate the perceptions, instructional knowledge and classroom practices of English teachers in teaching reading in rural areas in Sabah. An online survey was conducted on a sample of 20 secondary English teachers in a teacher professional development programme in Kudat, Sabah. The implications of these findings for future practice in rural high schools are discussed.